Prevalence and predictors of preconception medical and behavioral risks among soon-to-be married couples: A quantitative cross-sectional survey in Rwanda - Richard Nsengiyumva; Thiery Claudien Uhawenimana; Olive Bazirete; Darius Gishoma; Carlsson Ing-Marie; Lee HaEun; Jody Rae Lori (PLoS ONE, 2026)
Background Maternal and neonatal morbidities and mortality remain a global public health concern. Although preconception risk assessment has been found to enhance maternal, fetal, neonatal, and child health outcomes, few studies have explored preconception risks among premarital couples. The purpose of this study was to investigate the prevalence and predictors of preconception medical and behavioral risks among soon-to-be-married couples. Methods A quantitative cross-sectional survey of 623 couples attending prenuptial meetings in rural and urban settings (churches and sector offices) was conducted from May to June 2024 using multistage cluster and purposive sampling. Data in the form of self-reported information were collected via structured interviewer-administered questionnaires. The Statistical Package for the Social Sciences (SPSS), version 29, was used to analyze the data. Results Most participants (64%) were aged 21–30, with 81.5% from rural areas. Nearly half (49.3%) were classified as high-risk. Common medical risks included mental stress (46%), underweight (21.7%), use of teratogenic medications (16.1%), diabetes (12.5%), and hypertension (9.9%). Over 90% had never been screened for syphilis, hepatitis, anemia, or taken folic acid. Behavioral risks included inadequate nutrition (41%), heavy alcohol use (29%), use of non-prescribed/herbal medications, exposure to hazardous environments (20%), and inadequate physical activity. Males (OR = 1.28, p = .033) and urban residents (OR = 1.37, p = .011) had higher odds of risk. Shorter time until marriage was linked to increased risks (OR = 0.59, p < .001), while awareness of preconception care (OR = 0.09, p = .023) and medium-to-high income (OR = 0.79, p = .042) were associated with reduced risk. Conclusion The overall prevalence of preconception risks among engaged couples was found to be high, indicating a need for targeted clinical and educational interventions for early prevention and management.